Case Report: Pericardial patch repair of mitral annulus and mitral valve for a left atrial dissection caused by parasitic infective endocarditis - Chu, PeiShan; Tang, Yi; Liu, XinPei; Miao, Qi (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Left atrial dissection is a rare event, typically associated with cardiac manipulation. We report the first case of a left atrial dissection caused by parasitic infectious endocarditis, which required the use of patch repair for the damaged mitral annulus and valve.Case Presentation: To treat heart failure in a 43-year-old man with left atrial dissection, we performed a patch repair of the mitral annulus and valve using autologous pericardium.Conclusion: we encourage novel surgery for complicated infectious endocarditis.